PENERAPAN MODEL PEMBELAJARAN KOOPERATIF TIPE THINK PAIR SHARE UNTUK MENINGKATKAN HASIL BELAJAR PESERTA DIDIK PADA MATERI USAHA DI SMP NEGERI 1 SUBAH - Elga Kristine; Edy Tandililing; Muhammad Musa Syarif Hidayatullah (Jurnal Pendidikan dan Pembelajaran Khatulistiwa (JPPK), 2021)
AbstractThis study aims to find out if the cooperative learning model of think pair share type can improve the learning outcomes of students in business materials in Grade VIII SMP Negeri 1 Subah. The form of research used is quasi experimental design with nonequivalent control group design. Samples in the study through simple random sampling techniques and selected based on recommendations from science. The test in this study is in the form of 5 essay questions. Based on the data reference, it is concluded (1) The gain of learners' learning results on business materials before the granting of a think pair share type cooperative learning model is 47.72 while the acquisition of learners' learning outcomes on business materials before being given conventional learning is 44.54 and the acquisition of learning results on business materials after being given a cooperative learning model type think pair share is 70.90 while the acquisition of learning results of learners in business materials after being given conventional learning is 61.47. (2) There are differences in learning outcomes in business materials between students who follow a think pair share type cooperative learning model with students who follow conventional learning. (3) Based on the results of the effect size test of 1.2 is categorized as high. This shows that the cooperative learning model of think pair share type can be used effectively to improve the learning outcomes of business material students in grade VIII SMP Negeri 1 Subah.Keywords: Cooperative Learning Model Type Think Pair Share, Learning